Comparative pathological changes in sheep infected with Theileria annulata and non-infected control - AKHTER, W.; ASLAM, A.; REHMAN, M. U.; REHMAN, H. U.; RASHID, I.; AKHTAR, R. (Journal of the Hellenic Veterinary Medical Society, 2018)
The hematological, serum biochemical and histopathological variations were compared in sheep naturally infected with Theileria annulata and healthy control group. Peripheral blood smears of 300 suspected sheep were observed for the presence of Theileria by microscopy (24%) and confirmed through PCR (34%). The PCR confirmed samples were used for further studies and showed significant decrease in hemoglobin concentration, packed cell volume (PCV), total erythrocyte counts, total leukocyte count, serum total proteins, creatinine and glucose (P < 0.05) as compared to healthy control. Similarly a significant increase was recorded in Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (P< 0.05) as compared to non-infected sheep. Histopathological changes revealed edema and severe depletion of lymphocytes in lymph nodes. The present study concluded that ovine theileriosis was linked with some pathological alterations in blood and tissues which could be helpful in the diagnosis of disease.